Respuesta :

A0FE
Answer:
-2/3

Step by step explanation:
Distribute first: 3q+4=2
2-4=-2
-2/3=-2/3

Answer: q = -2/3

Step-by-step explanation: To find q, we first need to remove the parentheses on the left side of the equation. We can do this by multiplying everything outside the parentheses by everything inside them.

3 (q + 4/3) = 2

3q + 3 · 4/3 = 2

3q + 4 = 2

Now, we need to move the 4 to the other side of the equal sign. To do this, we just need to change its sign when moving it:

3q = 2 - 4

3q = -2

All we have to do next is divide both sides of the equation by 3 so we can fully isolate the q:

3q/3 = -2/3

q = -2/3

ACCESS MORE